2019
DOI: 10.3390/ijms20174275
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Microencapsulated B. Longum BAA-999 and Lycopene Modulates IGF-1/IGF-1R/IGFBP3 Protein Expressions in a Colorectal Murine Model

Abstract: The Insulin-like growth factor-I/Insulin-like growth factor-I receptor (IGF-1/IGF-1R) system is a major determinant in colorectal cancer (CRC) pathogenesis. Probiotics (Bifidobacterium longum, BF) and lycopene (LYC) have been individually researched for their beneficial effects in the prevention of CRC. However, the effect of a combined treatment of microencapsulated BF and LYC on IGF-1/IGF-1R/IGFBPs (Insulin-like growth factor-binding proteins) expression in an azoxymethane (AOM)-dextran sulfate sodium (DSS)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In addition, DSS causes bloody diarrhea, ulcerations, and heavy infiltration of inflammatory cells into the mucosa [62], suggesting that inflammation is involved in the tumor-promotion activity of DSS. Similar results have been observed in our study and by others in the AOM/DSS-induced CRC mouse model [38][39][40]63,64].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, DSS causes bloody diarrhea, ulcerations, and heavy infiltration of inflammatory cells into the mucosa [62], suggesting that inflammation is involved in the tumor-promotion activity of DSS. Similar results have been observed in our study and by others in the AOM/DSS-induced CRC mouse model [38][39][40]63,64].…”
Section: Discussionsupporting
confidence: 93%
“…As we previously reported, increased β-GA and pH values have been related to the carcinogenic effect of the AOM in the presence of DSS [38]. Therefore, β-GA and pH values in fecal, cecal, and colonic samples collected before and during the euthanizing of the animals were also determined, and the results are shown in Table 2.…”
Section: Effect Of Sprouted Oat (So) and Its Phenolic Ava Extract (Avmentioning
confidence: 91%
“…Similarly, for high dosage, there was a significant spike in positive rates of IGF-1, IGF-2 and IGFBP3 despite a significant reduction in IGFBP2. There was no change in the number of tumors or adenocarcinomas incidence but there was noticeable focal necrosis present in colonic tissue [79]. The anti-cancer effect of lycopene in this experiment could be said to be moderate as there were both positive and negative outcomes, accompanied by its ineffectiveness in reducing the number of tumors and adenocarcinomas incidence.…”
Section: Animal Studiesmentioning
confidence: 61%
“…Notably, previous research has shown that lycopene intake increases serum total IGFBP3 concentrations in clinical trials and basic research. 27 , 28 The presence and abnormal expression of pro-inflammatory gene, such as FOXO1 in the tumor microenvironment is consistent event within a maladjustment of chronic cellular immune response. 29 , 30 It is identical to this study.…”
Section: Discussionmentioning
confidence: 99%